Um agente pedagógico gentil é mais efetivo? Efeito das atitudes de agentes pedagógicos animados na aprendizagem, engajamento, emoções e ansiedade dos estudantes - Azevedo, Otávio Bastos (Universidade do Vale do Rio dos Sinos, 2020)
The affective attitudes of teachers can have a positive or negative impact on students’ learning. Therefore, it is a good practice to consider them when designing animated pedagogical agents. According to the number of publications in this area since 2014, the interest in animated agents with affective dimensions has increased considerably in recent years. However, there was no comparison of the effects of animated pedagogical agents with opposite attitudes (such as friendly and direct, for example) and neutral (without emotions). Thus, the objective of this work is to verify the impact of the animated pedagogical agents attitudes on students in relation to learning, engagement, emotions and state of anxiety. To achieve this goal, an agent with friendly, direct and neutral attitudes was developed and integrated with the PAT2Math Intelligent Tutor System. This system was used in an experimental evaluation involving 71 students of the seventh grade of elementary school, which were distributed in three groups, one for each agent’s attitude. The results indicated that the students in the friendly agent group showed greater engagement and learning gain. There was also a greater intensity of positive emotions in students who used friendly and direct agents. In addition, a reduction in anxiety was identified for students in the neutral agent group and for students who used the friendly agent in the first stage of the experiment. However, no statistically significant differences were identified in most comparisons, possibly due to the small sample size.
Keywords: Agente pedagógico animado; Computação afetiva; Atitudes; Amigável; Direta; Neutra; Sistema tutor inteligente; Animated pedagogical agent; Affective computing; Attitudes; Friendly; Direct; Neutral; Intelligent tutoring system; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação